Menuju Asean Economic Community 2015 dalam Kondisi Pembangunan Ekonomi yang Timpang - Stanislaus Risadi Apresian (Jurnal Ilmiah Hubungan Internasional, 2014)
Abstract: Economic development gap has divided ASEAN countries into two groups namedASEAN-6 and CLMV. Yet, ASEAN is still in the process to establish ASEAN Economic Community(AEC) in 2015. And in attempt to establish AEC, equitable economic development becomes one of themain characteristics in AEC Blueprint. A debate then arises whether ASEAN is plausible to establisheconomic community successfully or not. In fact, development gap does not always obstruct theestablishment of a community. As for an example, development gap also exists in European region butit is not regarded as a serious problem that can hinder European countries to establish European Union.This study is aimed at discussing the influences of economic development gap among ASEANcountries towards the process of AEC establishment. In this study, dependent development theory ofCardoso is used to analyze the development gap in ASEAN. Based on further analysis, it is found thatthe development gap in ASEAN is influenced by the international economic structure. Data shows thatASEAN countries are integrated (in?)to international structure through the foreign direct investmentfrom the center states. This condition places ASEAN countries as the dependent countries.Key Words: development gap, ASEAN Economic Community (AEC), dependent development